Interrogating Factors Affecting the Choice and Utilisation of Online Learning Technologies for A Higher Education Institution - Maphosa, Cosmas; Rugube, Talent; Mthethwa-Kunene, Khetsiwe Eunice; Dlamini, Patience (Advances in Social Sciences Research Journal, 2021)
ABSTRACT This desktop review paper advances the view that the utilisation of technology for online teaching and learning needs to be based on sound considerations. Online learning technologies are defined and the purpose of utilising such technologies is explored. Among the different considerations in online technology utilisation is the need to consider how the technologies assist in solving pedagogical challenges for teaching and learning. The context in which the learners and the course instructors find themselves using the technologies may promote or negate the effective use of the technology. Technology may be costly to procure and maintain, and this factor should be considered before the technology is procured for use in an institution of higher education. In many contexts, especially in sub-Saharan Africa, the digital divide is real in terms of access to technologies and the skills in technology use. The use of technology may perpetuate social differences as learners from disadvantaged backgrounds end up being left out of the learning process. Organisational and infrastructural issues are other important factors to consider in technology utilisation. The paper concludes that technology utilisation for online teaching and learning should be deliberately planned to consider numerous factors and address avoidable challenges in the implementation of online learning.